Peran Pemerintah Desa Terhadap Pengelolaan Pasar Tradisional Tanah Lot, Desa Beraban, Kecamatan Kediri, Kabupaten Tabanan - I Made Suamba; Ni Made Dwi Widari (Jurnal Widya Mahavira, 2025)
This study examines the role of the Beraban Village government in the management of the Tanah Lot Traditional Market using a qualitative descriptive approach with observation and interview techniques. Based on the theory of role and management, this study aims to analyze the role and efforts of the village government in managing the traditional market. The results of the study show that the Beraban Village government plays an active role in the management of the Tanah Lot Traditional Market. This can be seen from the high concern for the market which has a complete complement of traders and a diversity of merchandise, making it one of the most visited traditional markets compared to other markets in South Kediri District. However, even though management efforts have been carefully planned with market managers, the principles of efficiency and effectiveness have not been optimal. The manager has not been able to make the most of the available facilities, so the expected goals have not been fully achieved. The conclusion of the study shows that the Beraban Village government has shown an active role, while the market management has quite good management but still needs optimization to achieve maximum and effective management.